Alaric the Goth: An Outsider's History of the Fall of Rome - Boin, Douglas (New York : W. W. Norton & Company, 2020)
"Did "barbarians" really cause the catastrophic collapse of civilization? Boin is the first to give an historically sound account from the "barbarian" perspective, through the life of Alaric the Goth. On August 24, 410 A.D., the Senate and the People of Rome awoke to a seismic shock. Intruders, led by a disaffected forty-year-old immigrant, known only as Alaric, had stormed the city. There were kidnappings, robbery, and acts of arson. The effects were long-lasting. Within two generations, Rome's world fell apart. A city predicted to rule an empire without end, in the words of its famous Latin poet Virgil, was governed by a savage band of foreigners, called Goths. Alaric the Goth offers a deeply researched look at the end of the Roman Empire but from a surprising point-of-view. Offering the first full-length biography of Alaric, a talented and frustrated immigrant living in a time of pervasive bigotry, state-supported Christian violence, and irrational xenophobia, it breaks out of decades of tired, traditional approaches to the period, most of which overidentify with the Roman people. And it reveals the lasting contributions Goths made to legal history, to the values of religious toleration, and to modern ideas of citizenship. By moving this man from the borders to the center of Rome's story, it asks readers to think deeply and differently about the lives of marginalized people too often invisible in our history books."
Keywords: Visigoths -- Biography. -- Kings and rulers; Rome -- History -- Germanic Invasions, 3rd-6th centuries